Active and Passive Voice in Reporting Clauses in Newspaper Reports - Truksasová, Kateřina (Univerzita Pardubice, 2012)
This bachelor paper is focused on the occurrence of active and passive voice in reporting clauses in newspaper reports in British broadsheets. The theoretical part is divided into three main chapters. Firstly, the discourse of newspaper reports and the function of reported language in this type of discourse is described. Secondly, the attention is paid to direct, indirect and free indirect categories of speech, writing and thought presentation. The last chapter deals with active and passive voice. The theory presented in the first part is applied to the analysis. The aim of the practical part is to explain the occurrence of active and passive voice in reporting clauses in newspaper reports.
Činný a trpný rod v uvozovacích větách v duskurzu novinových článků
Keywords: činný rod; trpný rod; uvozovací věty; reprodukce řeči; novinové články; active voice; passive voice; reporting clause; reported language; newspaper reports